Food restriction alters salivary cortisol and α-amylase responses to a simulated weightlifting competition without significant performance modification. Issue 5 (4th March 2018) - Durguerian, Alexandre; Filaire, Edith; Drogou, Catherine; Bougard, Clément; Chennaoui, Mounir
ABSTRACT: The aim of this investigation was to evaluate the effect of a 6-day food restriction period on the physiological responses and performance of 11 high-level weightlifters. After a period of weight maintenance ( T 2 ), they were assigned into two groups depending on whether they lost (Diet group, n  = 6) or maintained their body weight (Control group, n  = 5) during the course of those 6 days. An evaluation of performance and the measurement of salivary cortisol concentrations and salivary α-amylase (sAA) activity were performed during a simulated weightlifting competition which took place at T 2, after a 6-day period of food restriction ( T 3 ). Dietary data were collected using a 6-day diet record. We noted a 41.8% decrease in mean energy intake during the dietary restriction period, leading to a 4.34% weight loss for the Diet group. Dietary restriction did not modify absolute performance levels, whilst a significant improvement was noted for the Control group. Furthermore, we noted a response of decreased salivary cortisol and increased sAA activity to the simulated competition stress at T 3 for the Diet group. These results may indicate that dietary reduction led to a dissociation of the hypothalamo-pituitary-adrenal axis and the sympatho-adreno-medullary system, which could impair training adaptations and absolute performance development.